ANALISIS USER INTERFACE PADA WEBSITE STAINU PACITAN MENGGUNAKAN METODE EIGHT GOLDEN RULES - Candra Budi Susila (Universitas Islam Balitar Blitar, 2020)
Analysis of the user interface on the Pacitan STAINU website is a study that aims to analyze an interface on the Pacitan STAINU website. The STAINU website itself is one of the information media for lecturers and students to provide all information related to campus academic activities. The analysis used in this study uses the Eight Golden Rules or 8 golden rule principles developed by Ben Shneiderman in order to test whether the user interface on the web is in accordance with the wishes of the user. The results of the analysis found that the average recipes stated good. This is obtained based on the results of data analysis on each variable, namely for consistency variables with a value of 147.5, Shortcut Variables with a value of 161, Feedback Variables with a value of 160.5, Closure Dialogue Variable with a value of 166.5, Simple Error Handling Variables with a value of 161, Resersible Action Variables with values 157, Put User In Control variable with value 161, Reduce Variable Short Term